The #Path2Path Virtual Landscape During the COVID-19 Pandemic: Preparing for the 2020 Pathology Residency Recruitment Season - Hannah Cutshall BS; Reagan Hattaway BS; Nikhi P. Singh BS; Soroush Rais-Bahrami MD; Brandi McCleskey MD (Elsevier, 2021)
On May 11, 2020, the Association of American Medical Colleges released recommendations discouraging in-person activities for away rotations and mandating virtual-only residency recruitment interviews. This paper focuses on how residency programs have attempted to adjust to this vastly different application cycle by using social media to reach their applicants. A total of 138 programs were identified through the Electronic Residency Application Services. The presence of Departmental/Residency program Twitter, Instagram, and Facebook as well as web pages offering virtual opportunities was recorded for each program on October 30, 2020. A total of 132 social media accounts were found; the majority of which were on Twitter, while fewer were on Instagram and Facebook. All 138 pathology residency programs had websites. Sixteen (11.5%) of those advertised virtual open houses and 2 (1.4%) advertised virtual subinternships; social media were more often used for advertisement of these virtual experiences. A total of 58 open house opportunities were advertised on Twitter, 21 on Instagram, and 20 on Facebook. Innovative virtual subinternships ranging from 2 to 4 weeks were developed, but only represented 6% of the usual 126 away rotations available. Pathology programs across the country utilized websites and social media as a method of communication to interact with applicants as part of the #Path2Path in 2020 and to provide virtual opportunities in preparation for a drastically different recruitment cycle.